PENGARUH AUDIT REPORT LAG DAN KUALITAS AUDIT TERHADAP AUDITOR SWITCHING (STUDI EMPIRIS PADA PERUSAHAAN YANG TERCATAT DI INDEKS KOMPAS 100 BURSA EFEK INDONESIA TAHUN 2020-2022) - Sagala, Clarissa Grace S.; Malau, Harman; Siagian, Harlyn L. (FEB Universitas Sam Ratulangi Manado, 2024)
This research aims to examine the effect of audit report lag and audit quality on auditor switching among companies listed in the Kompas 100 Index of the Indonesia Stock Exchange for the years 2020-2022. With a quantitative approach and utilizing secondary data, this research successfully gathered samples from 51 companies, representing a total of 153 data samples, from the entire population of 100 companies, through purposive sampling technique. The analytical method employed in this research is logistic regression analysis. According to the results, the Nagelkerke R Square of 0.061 indicates that audit report lag and audit quality can only explain 6.1% of the influence on auditor switching, while 93.9% is influenced by other variables outside of this study. The findings shows that neither audit report lag nor audit quality significantly affects auditor switching, both partially or simultaneously. Keywords: Audit Report Lag, Audit Quality, Auditor Switching